Impact of COVID-19 among Nurses - Panta, Ganga; Panta, Ramesh (Journal of Nursing Education of Nepal, 2022)
Background:The corona virus disease (COVID-19) is a highly contagious disease with mild to fatal effects to the people around the world. Unavailability of medicine and uncertainty of disease made the life of nurses more stressful leading to disruption on emotional, social and family health. This article intended to assess the impact of COVID-19 among nurses. Methods:Total 55 original, review and other articles were searched through electronic database like PubMed, Research Gate and google scholar. Among them, 19 relevant articles were selected then critically analysed, cited and prepared a reference list by using Zotero software. After thoroughly reviewing those articles different impacts among nurses around the world related to COVID-19, were analyzed and organized in this article. Results: Nurses experienced tremendous fear and anxiety for the safety of themselves and their family members. Likewise, stigma related to COVID-19 affects the emotional and family health of the nurses. Thus, nurses should be adequately prepared to battle such pandemic situations and they should be supported emotionally and socially including organization enrichment. Adequate resources are indispensable for the better adjustment with such pandemic situations like COVID-19. Conclusion: Organization support with adequate resources including community awareness against social stigma is indispensable to support the nurses during such pandemic situation.